2020
DOI: 10.1038/s41598-020-61866-7
|View full text |Cite
|
Sign up to set email alerts
|

Resting-state EEG activity predicts frontoparietal network reconfiguration and improved attentional performance

Abstract: Mounting evidence indicates that resting-state EEG activity is related to various cognitive functions. To trace physiological underpinnings of this relationship, we investigated EEG and behavioral performance of 36 healthy adults recorded at rest and during visual attention tasks: visual search and gun shooting. All measures were repeated two months later to determine stability of the results. Correlation analyses revealed that within the range of 2-45 Hz, at rest, beta-2 band power correlated with the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 82 publications
(68 reference statements)
3
42
0
Order By: Relevance
“…Theoretical considerations indicate that strong EEG connectivity in the beta-2 band is highly stable 44 , 45 , less prone to disturbance 44 , 46 and consequently results in less dynamic processing and behavior 47 , 48 . This lower reconfiguration capability is also in line with our previous investigation which showed that subjects with stronger PLVs exhibited less flexible connection patterns 49 . Negative correlations between the strength of EEG connectivity and performance in attention and memory tasks has been confirmed in ADHD patients 50 – 52 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Theoretical considerations indicate that strong EEG connectivity in the beta-2 band is highly stable 44 , 45 , less prone to disturbance 44 , 46 and consequently results in less dynamic processing and behavior 47 , 48 . This lower reconfiguration capability is also in line with our previous investigation which showed that subjects with stronger PLVs exhibited less flexible connection patterns 49 . Negative correlations between the strength of EEG connectivity and performance in attention and memory tasks has been confirmed in ADHD patients 50 – 52 .…”
Section: Discussionsupporting
confidence: 91%
“…These studies showed that strong parietal and occipital connectivity correlated with inattention type ADHD. In the context of the current study, the decision by Pandemics to continue engagement in the study, despite risk, could be reinforced by a lower reconfiguration capability of neuronal networks and subsequently, reduced capacity to adjust their behavior to current environmental conditions 49 . Thus, lower network reconfiguration capacity, combined with higher extraversion appear to be associated with the decision to continue participation in this study.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, in non-human primates, a visual search task that engaged top-down attentional processes was associated with stronger high beta activity across frontal and parietal dorsal regions ( Buschman and Miller, 2007 ). Similarly, in humans, high beta oscillatory power correlated with frontoparietal connectivity and behavioral performance on a visual search and shooting task ( Rogala et al, 2020 ). Furthermore, using TMS bursts to increase synchronization of high beta oscillations, several studies have demonstrated stronger long-range high beta synchronization between both the bilateral parietal cortices and a network including the right frontal eye field and right parietal region led to increased visual perception and detection ( Quentin et al, 2015 ; Stengel et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%